2014
DOI: 10.1111/nep.12232
|View full text |Cite
|
Sign up to set email alerts
|

Resistance factors for the treatment of immunoglobulin A nephropathy with diffuse mesangial proliferation

Abstract: Our results, although based on only a small number of patients in a retrospective study, suggest that age, presence of C3 deposits and interstitial changes at the onset, and persistent renal inflammatory activation may be risk factors for non-responsiveness to treatment for IgAN with diffuse mesangial proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…In paediatric IgAN, infiltrating interstitial and glomerular macrophages are associated with unfavourable evolution,persistent inflammatory activation and proteinuria . We have demonstrated that E score largely reflects glomerular inflammation and that CD68 + cells participate in renal infiltrates; median endocapillary CD68 + counts were associated with the extent of endocapillary hypercellularity.…”
Section: Discussionmentioning
confidence: 81%
“…In paediatric IgAN, infiltrating interstitial and glomerular macrophages are associated with unfavourable evolution,persistent inflammatory activation and proteinuria . We have demonstrated that E score largely reflects glomerular inflammation and that CD68 + cells participate in renal infiltrates; median endocapillary CD68 + counts were associated with the extent of endocapillary hypercellularity.…”
Section: Discussionmentioning
confidence: 81%
“…We also found that 89% of children with severe IgAN treated with combination therapy, consisting of prednisolone, mizoribine, warfarin, and dipyridamole, had no or only mild proteinuria, and reported that combination therapy had improved the long -term outcome of IgAN 10) . In other words, these findings suggested that few patients 72 Y.…”
Section: Discussionmentioning
confidence: 81%
“…The prognosis of most severe cases of pediatric IgAN treated with multi -drugs combination therapy is good ; however, some patients with severe IgAN experience recurrence after combination therapy or resistance to treatment. We also showed that 11% of children with severe IgAN treat-Long prognosis of tonsillectomy plus pulse therapy ed with combination therapy, consisting of prednisolone, mizoribine, warfarin, and dipyridamole, had the relapse of IgAN 10) , and there have been few reports on adequate treatments for these IgAN patients.…”
Section: Introductionmentioning
confidence: 99%
“…Yoshikawa et al . reported the beneficial effects of multiple‐drug therapy consisting of prednisolone, azathioprine, heparin‐warfarin, and dipyridamole in the treatment of severe pediatric IgAN, and we previously reported that prednisolone, warfarin, and dipyridamole therapy combined with mizoribine (PWDM) was effective in ameliorating proteinuria and histological severity in children with IgAN on short‐term follow up, and showed that only 11% of children with severe IgAN treated with PWDM had IgAN relapse at long‐term follow up …”
mentioning
confidence: 89%
“…There have been many reports on the treatment of pediatric IgAN. Since 1990, corticosteroids, immunosuppressive agents, antiplatelet drugs, and anticoagulation agents have been used alone or in combination to treat IgAN . Yoshikawa et al .…”
mentioning
confidence: 99%